Incentive Effects of Bonus Payments : Evidence from an International Company - Axel Engellandt; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2004)
This study uses panel data describing about 6,500 employees in a large international company to study the incentive effects of performance related pay. The company uses two performance related remuneration mechanisms. One is an individual "surprise" bonus payment. The other is a more structured system, where part of the salary is determined by individual performance evaluations. We hypothesize that effort is higher in departments where (i) performance evaluation results are more spread out, (ii) person-specific performance evaluations are more flexible over time, (iii) surprise bonuses are used more frequently. These hypotheses are tested using days of absence and overtime work as effort indicators. The tests yield that hypotheses (ii) and (iii) are supported, and that (i) cannot be tested reliably due to possible simultaneity bias in our data. We investigate and confirm the robustness of these findings. They suggest that surprise bonus payments and flexibility in the evaluation of individual performances over time provide effective incentives for employee effort.
Keywords: C25; J33; M50; J41; J24; M12; 330; bonus; merit pay; pay for performance; worker effort; social status; mobility; absenteeism; overtime; Leistungsorientierte Vergütung; Leistungsanreiz; Vergütungssystem; Multinationales Unternehmen; Schätzung; Schweiz